2016
DOI: 10.1093/ageing/afw223
|View full text |Cite
|
Sign up to set email alerts
|

Using quality assessment tools to critically appraise ageing research: a guide for clinicians

Abstract: Evidence based medicine tells us that we should not accept published research at face value. Even research from established teams published in the highest impact journals can have methodological flaws, biases and limited generalisability. The critical appraisal of research studies can seem daunting, but tools are available to make the process easier for the non-specialist. Understanding the language and process of quality assessment is essential when considering or conducting research, and is also valuable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…SR and MA summarizing the evidence from multiple trials have been published since the 70s, but the methodological quality of those type of studies began to be discussed around 20 years later, which finally lead to the publication of the first version of the AMSTAR Instrument in 2007 . The methodological quality consists of items such as the design and conduct of research, and it is fundamental for physicians to understand the results and the level of confidence in the findings . Thus, the methodological quality' definition is the extent to which an SR is designed in a way enabling producing unbiased results .…”
Section: Discussionmentioning
confidence: 99%
“…SR and MA summarizing the evidence from multiple trials have been published since the 70s, but the methodological quality of those type of studies began to be discussed around 20 years later, which finally lead to the publication of the first version of the AMSTAR Instrument in 2007 . The methodological quality consists of items such as the design and conduct of research, and it is fundamental for physicians to understand the results and the level of confidence in the findings . Thus, the methodological quality' definition is the extent to which an SR is designed in a way enabling producing unbiased results .…”
Section: Discussionmentioning
confidence: 99%
“…Studies were reviewed to determine whether the cohort observed was representative of the study population and whether there was risk of bias in the recruitment process or identification of the exposure to hypoglycaemia . Bias and methodological assessment was completed by two reviewers (AL and CB) using an adapted version of the Newcastle–Ottawa scale .…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the heterogeneity and research methods of previous studies, we chose to use the Cochrane Collaboration Handbook and Critical Appraisal Skills Program (CASP) [15]. Based on the appropriate checklists, we focused on selection, detection, and measurement bias; limited and residual confounding; as well as on statistical power and causality between exposures and outcomes.…”
Section: Quality Of Studiesmentioning
confidence: 99%